Effects of tungsten addition on the microstructural stability and properties of Ti-6.5Al-2Sn-4Hf-2Nb-based high temperature titanium alloys. (10th December 2021) - Xu, Yaqun; Fu, Yu; Li, Juan; Xiao, Wenlong; Zhao, Xinqing; Ma, Chaoli
Abstract: The microstructural evolution, oxidation resistance and mechanical properties of Ti-6.5Al-2Sn-4Hf-2Nb-based alloys with different contents of tungsten (W) additions ranging from 0 to 4.0 wt.% have been investigated in this study. The addition of W changed the microstructure from Widmanstätten colony of the W-free alloy to basketweave microstructure. After thermal exposure at 650 °C for 1000 h, the retained β phase became less continuous, and secondary β nano-particles with high W concentration were precipitated from α lamellas. Within α lamellas, the W was found to mainly partitioned into the secondary β phase and refined the ordered α2 -Ti3 Al precipitates due to increased solubility of Nb in α2 phase. High W addition increased activation energy for oxidation, promoting the formation of more uniform and compact compound oxides, therefore substantially enhanced the oxidation resistance of the alloy. Besides, the W addition also improved the room and high-temperature yield strength without obviously losing plasticity after long-time thermal exposure. The improved mechanical performance was mainly attributed to the introduction of more α/β interfaces, the precipitation of secondary β phase and the refined α2 phase with Nb segregation. Highlights: Ti-Al-Sn-Hf-Nb-based high temperature titanium alloys with different W additions were studied. W addition promoted secondary β precipitation and refined ordered α2 phase. High W content substantially improved the oxidation resistance. W addition improved yield strength without obviously losing plasticity. Graphical abstract: Image, graphical abstract